Tungsten Blocks Murine B Lymphocyte Differentiation and Proliferation Through Downregulation of IL-7 Receptor/Pax5 Signaling. (26th March 2019) - Wu, Ting Hua; Bolt, Alicia M; Chou, Hsiang; Plourde, Dany; De Jay, Nicolas; Guilbert, Cynthia; Young, Yoon Kow; Kleinman, Claudia L; Mann, Koren K
Abstract: Tungsten is an emerging environmental toxicant associated with several pediatric leukemia clusters, although a causal association has not been established. Our previous work demonstrated that tungsten exposure resulted in an accumulation of pre-B cells in the bone marrow, the same cell type that accumulates in pediatric acute lymphoblastic leukemia (ALL). To better understand the relevant molecular mechanisms, we performed RNA-sequencing on flow sorted pre-B cells from control and tungsten-exposed mice. Tungsten decreased the expression of multiple genes critical for B cell development, including members of the interleukin-7 receptor (IL-7R) and pre-B cell receptor signaling pathways, such as Jak1, Stat5a, Pax5, Syk, and Ikzf3 . These results were confirmed in an in vitro model of B cell differentiation, where tungsten arrested differentiation at the pro-B cell stage and inhibited proliferation. These changes were associated with decreased expression of multiple genes in the IL-7R signaling pathway and decreased percentage of IL-7R, phosphorylated STAT5 double-positive cells. Supplementation with IL-7 or overexpression of Pax5, the transcription factor downstream of IL-7R, rescued the tungsten-induced differentiation block. Together, these data support the hypothesis that IL-7R/Pax5 signaling axis is critical to tungsten-mediated effects on pre-B cell development. Importantly, many of these molecules are modulated in ALL.